Comparison of ultrasonography and Intravenous urography in predicting the outcome of Extracorporeal Shockwave lithotripsy in nephrolithiasis - Lynser, Donboklang; Singh Sinam, Sekharjit; Singh, L. Surendra (International Journal of Medical Research and Review, 2015)
Introduction: ultrasound has a well established role in evaluating the kidney. Calculus is readily picked up on ultrasound. Normal sonographic features with doppler detection of ureteric jets indicate presence of normal renal function. Using these advantages we undertook this present study to determine whether ultrasound (USG) can replace intravenous urography (IVU) in the pre-operative evaluation of extracorporeal shockwave lithotripsy (ESWL) patients. Methods and Material: This study was a prospective observational study conducted in the Department of Radiodiagnosis, Regional Institute of Medical Sciences (RIMS), Imphal, during a period of 2 years. 50 patients with confirmed renal stones referred for ESWL treatment in the Department of Urology, RIMS, Hospital, Imphal were included. USG and IVU were independently interpreted. Cases were grouped as excellent, good, borderline or poor cases. Sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of USG and IVU are compared. Results: The sensitivity and specificity of ultrasound in predicting the outcome after ESWL for solitary renal calculus is 95.8% and 50% respectively with a PPV and NPV of 97.8% and 33.33% respectively and the sensitivity and specificity of IVU in predicting the outcome after ESWL are 97.9% and 50% respectively with a PPV and NPV of 97.8% and 50% respectively. Conclusions: USG can be the alternative radiological examination in the pre-operative evaluation of ESWL patients as the USG and IVU have comparable predictive values.